Identification of biallelic variations of CEP70 in patients with male infertility - Ruan, Tiechao; Yang, Yihong; Jiang, Chuan; Shen, Gan; Li, Dingming; Shen, Ying (Frontiers in Endocrinology, 2023)
Introduction: Male infertility is a severe health issue caused by complex and multifactorial pathological conditions. Genetic factors are a major cause of male infertility. CEP70, a centrosomal protein, has been reported to play an important role in male reproduction in mice. However, the role of CEP70 in human male infertility is limited. Methods: Whole exome sequencing and Sanger sequencing were used to identify the genetic cause of the infertile patients. Papanicolaou staining, scanning electron microscopy and transmission electron microscopy were further conducted to explore morphological and ultrastructural defects in spermatozoa from the patient. Immunofluorescence staining was used to detect the pathogenicity of the identified variants and the particular expression of CEP70 in testis. Results: In this study, we identified biallelic mutations of CEP70 in two unrelated infertile male individuals with oligoasthenoteratozoospermia that followed a recessive inheritance pattern. Papanicolaou staining, scanning electron microscopy and transmission electron microscopy showed that morphological and ultrastructural defects in the acrosome and flagellum of sperm from the patient in a pattern strikingly similar to that in Cep70−/− male mice. The results of immunofluorescence staining suggested that CEP70 was normally expressed in the acrosome and flagellum of control sperm but was hardly detected in the sperm of patient carrying CEP70 variation. We also explored the particular expression pattern of CEP70 during spermatogenesis in humans and mice. Conclusions: Biallelic mutations of CEP70 might be a novel genetic cause of human male infertility, which could potentially serve as a basis for genetic counseling and diagnosis of male infertility.